Validity and Reliability of the Indonesian Short Form-Leeds Dyspepsia Questionnaire (SF-LDQ) - Prasetya, Ignatius Bima; Anas, Desriyadi; Al-Idrus, Syarifah Nur E’zzati; Simatupang, Flouria Stefanny; Herardi, Ryan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2025)
Background: The severity of dyspepsia symptoms is often overlooked despite established definitions and diagnostic criteria. The Short Form-Leeds Dyspepsia Questionnaire (SF-LDQ) is a validated English-language tool designed to evaluate these symptoms. This research focuses on creating and validating an Indonesian version of the SF-LDQ.Methods: The SF-LDQ was translated into Indonesian following standard procedures, including forward-backward translation, cross-checking, and pilot testing. Unselected patients from Dabo Regional Hospital and Dabo Lama Community Health Center (Pusat Kesehatan Masyarakat, or Puskesmas) completed a questionnaire upon enrollment and again after three days via direct follow-up or blinded phone interviews. Reliability was measured through internal consistency (Cronbach’s α) and test-retest analysis (Spearman’s correlation). Meanwhile, validity was evaluated by comparing SF-LDQ scores with Rome IV Criteria-based diagnoses from blinded physicians and analyzing diagnostic performance with ROC curves.Results: A total of 204 participants were included. The Indonesian SF-LDQ exhibited excellent reliability, with Cronbach’s α of 0.875 and Spearman’s correlation of 0.984 (p 0.001). Validity analysis demonstrated an AUC of 0.946 (p 0.001, 95% CI = 0.913–0.978). A cut-off score of 6.5 yielded 87.0% sensitivity and 93.3% specificity.Conclusion: The Indonesian SF-LDQ is a dependable and valid tool for evaluating the frequency and severity of dyspeptic symptoms.